Antropologi Politik Helmuth Plessner - Runesi, Yasintus T. (JAP UNWIRA, 2020)
In the contexts of contemporary social and political thought, a fundamental anthropological and political problem is thedebate about how deeply the essence of the human related to political praxis. The purpose of this article is to explore the idea ofHelmuth Plessner’s political anthropology as the middle paradigm, between political theology and economic theology. In thefirst and second parts of this article, Plessner’s philosophical anthropology will be presented, which focuses on the concept of theeccentric position of human being. Based on this concept, Plessner attempted to show the mutual interpenetration of philosophyand politics, which will be described in the third part of this article. Plessner insists on the importance of a philosophicalanthropology of the political for practical politics itself. Some conclusion will be drawn concerning the importance of smalldimensions of Plessner’s political anthropology in relation to the current political context.